Nilai Taroman pada Masyarakat Motaulun Kecamatan Malaka Barat Kabupaten Malaka - Febriana Hoar; Clotilde Seran (PT. ALHAFI BERKAH INDONESIA, 2023)
This study entitled the value of taroman in the Motaulun community, West Malacca District, Malacca Regency. The problems discussed in this study are who and how to carry out the taroman in the Motaulun community, what objects or tools are needed in carrying out the taroman ceremony and what values ​​are contained in the taroman ceremony? The results showed that the master of the garden performed the Taroman ceremony and the objects or tools used were wooden poles stuck in the middle of the garden, flat stones used as offering tables, betel and areca nut and green young coconuts. The value contained in the taroman activity is that the teligius value is a prayer of thanksgiving and a prayer of supplication.